Leisure-time physical activities and the risk of cardiovascular mortality in the Malmö diet and Cancer study - Sara Bergwall; Stefan Acosta; Stina Ramne; Pascal Mutie; Emily Sonestedt (BMC, 2021)
Abstract Background The association between leisure-time physical activity and cardiovascular mortality has been previously studied, but few studies have focused on specific activities and intensities. Methods The association between different leisure-time physical activities and cardiovascular mortality was investigated among 25,876 individuals without diabetes or cardiovascular disease from the population-based Malmö Diet and Cancer Study cohort. The individuals estimated the average duration spent on 17 physical activities at baseline in 1991-1996 and after 5 years. Cardiovascular mortality was obtained from a register during a mean of 20 years of follow-up. Results A total leisure-time physical activity of 15-25 metabolic equivalent task (MET) hours/week was associated with a decreased risk of cardiovascular mortality (HR 15-25 vs < 7.5 MET-h/week =0.80, 95% CI 0.69-0.93), with no further risk reduction at higher levels. Several high-intensity activities (i.e., lawn tennis and running) and moderate-intensity activities (i.e., golf, cycling and gardening) were associated with a reduced risk. Individuals who engaged in high-intensity physical activity for an average of 2.29 MET h/week (30 min/week) had an 18% (95% CI 0.72-0.93) reduced risk of cardiovascular mortality compared with non-participants, and no further risk reductions were observed at higher levels. Decreased risk was observed among individuals who had started (HR 0.56, 95% CI 0.32-0.97) or continued (HR 0.49, 95% CI 0.36-0.66) high-intensity activities at the five-year follow-up. Conclusions Moderate- and high-intensity leisure-time physical activities reduced the risk of cardiovascular mortality. With regard to total leisure-time physical activity, the largest risk reduction was observed for 15-25 MET-h/week (equivalent to walking for approximately 5 h/week).